Incarcerated Spigelian hernia: A rare cause of abdominal wall tender mass - Ender Anilir; Fatih Buyuker; Salih Tosun; Orhan Alimoglu (İstanbul Kuzey Klinikleri, 2020)
In this study, we aimed to present that incarcerated Spigelian hernia is an important cause of acute abdomen although it is rare and accounts for 1–2% of all abdominal wall hernias. Spigelian hernia arises from a defect in the aponeurosis of the transversus abdominis muscle, also known as the Spiegel fascia. This case analysis aims to present a Spigelian hernia case in which the sigmoid colon is incarcerated. The patient was referred to our emergency surgery clinic complaining of severe abdominal pain and a palpable mass in the left quadrant of the abdomen, presenting tenderness on the front abdominal wall. The symptoms suddenly emerged approximately eight hours ago before the patient was admitted to the hospital. The patient was taken into surgery after the ultrasonography (US) and computed tomography (CT) results suggested a preliminary diagnosis of incarcerated Spigelian hernia for which polypropylene mesh repair was performed. No recurrence was identified in the patient's control examination performed 22 months later. Incarcerated Speigel hernia should be considered as a cause for patients developing sudden stomach ache and mass, causing tenderness on the front abdominal wall for which mesh repair should be performed.